PERBANDINGAN RERATA PERTUMBUHAN BERAT BADAN BERDASARKAN PEMBERIAN BUBUR BAYI SEHAT PINGGIR JALAN Studi Cohort pada Bayi Usia 6-12 Bulan di Kelurahan Kalongan, Kecamatan Purwodadi, Kabupaten Grobogan - Safna Fadiyah; Sri Priyantini (Jurnal Riset Multidisiplin Edukasi, 2026)
Background: The practice of providing commercially sold roadside infant porridge has become an alternative complementary feeding option for parents due to its practicality and affordability; however, its nutritional adequacy and food safety remain uncertain. Objective: This study aimed to determine the difference in the mean body weight growth of infants aged 6–12 months between those who received complementary feeding practices and those who did not in Kalongan Village, Grobogan Regency. Methods: This research employed an analytic observational study with a cohort design. A total of 54 infants were selected based on inclusion and exclusion criteria. Body weight data were collected for three consecutive months. Data analysis was conducted using the Mann-Whitney test to assess the significance of differences in body weight growth between groups. Results: The findings showed that the mean body weight growth in the group that did not receive complementary feeding practices (0.24 kg) was slightly higher than that in the group that received them (0.19 kg). However, statistically, no significant difference was observed (p = 0.306). This result may have been influenced by external factors such as formula milk consumption and inconsistencies in the variety and composition of food ingredients used by vendors. Conclusion: The provision of complementary feeding practices did not demonstrate a significant difference in mean body weight growth among the study subjects. Therefore, future studies are recommended to conduct laboratory analyses to objectively determine the nutritional content of these complementary foods.